2014
DOI: 10.1002/path.4374
|View full text |Cite
|
Sign up to set email alerts
|

SKA1 over‐expression promotes centriole over‐duplication, centrosome amplification and prostate tumourigenesis

Abstract: Although spindle- and kinetochore-associated protein 1 (Ska1) has previously been identified as essential for proper chromosome segregation, it is unknown whether it plays a role in tumour development. Here, we report that Ska1 over-expression promotes prostate tumourigenesis. Immunohistochemistry and quantitative RT-PCR analysis revealed that Ska1 was over-expressed in human prostatic intra-epithelial neoplasia (PIN), the most likely prostate cancer precursor, and adenocarcinomas. Up-regulation of Ska1 protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 27 publications
1
32
0
Order By: Relevance
“…SKA1 was reportedly increased as a candidate oncogene in several common human cancers, contributing to various steps of oncogenesis and poorer prognosis 14‐18 . Not only SKA1 genomic mutations result in chromosome congression failure and subsequent cell changes, 33 but also SKA1 overexpression itself is primarily responsible for oncogenic function.…”
Section: Discussionmentioning
confidence: 99%
“…SKA1 was reportedly increased as a candidate oncogene in several common human cancers, contributing to various steps of oncogenesis and poorer prognosis 14‐18 . Not only SKA1 genomic mutations result in chromosome congression failure and subsequent cell changes, 33 but also SKA1 overexpression itself is primarily responsible for oncogenic function.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that SKA1 is involved in the growth and proliferation of various types of cancer, including oral adenosquamous and hepatocellular carcinoma, bladder cancer, gastric cancer, prostate cancer, thyroid cancer, non-small cell lung cancer, and glioblastoma. (44)(45)(46)(47)(48)(49)(50)(51) In the human genome, SKA1, SKA2, and SKA3 form the SKA complex. During mitosis, the SKA complex is localized between the outer kinetochore interface and the spindle microtubules.…”
Section: Discussionmentioning
confidence: 99%
“…The applied herein G 1 phase synchronization protocol differed from that applied in the case of LNCaP prostate cancer cells, by 7-hour longer growth in the regular media (Wang et al, 2016). The protocol applied in the case of S phase synchronization was analogous to those used by others (Chung et al, 2012;Li et al, 2014). The ABCC10 transcript was found to be expressed at a nearly identical level in asynchronous log-phase and S phase-synchronized CWR22Rv1 cell populations (Table 3).…”
Section: Resultsmentioning
confidence: 98%